Myeloablative chemotherapy for recurrent aggressive oligodendroglioma. - Cairncross, G. (2000)
The objective of this study was to ascertain the duration of tumor control and the toxicities of dose-intense myeloablative chemotherapy for patients with recurrent oligodendrogliomas. Patients with previously irradiated oligodendrogliomas, either pure or mixed, that were contrast enhancing, measurable, and behaving aggressively at recurrence were eligible for this study. Only complete responders or major partial responders (75 % reduction in tumor size) to induction chemotherapy--either intensive-dose procarbazine, lomustine, and vincristine or cisplatin plus etoposide-could receive high-dose thiotepa (300 mg/m2/day for 3 days) followed by hematopoietic reconstitution using either bone marrow or peripheral blood stem cells. Thirty-eight patients began induction chemotherapy and 20 (10 men, 10 women; median age 46 years; median Karnofsky score 80) received high-dose thiotepa. For the high-dose group, the median event-free, progression-free, and overall survival times from recurrence were 17, 20, and 49 months, respectively. Tumor control in excess of 2 years was observed in 6 patients (30%). Four patients (20%) are alive and tumor free 27 to 77 months (median, 42 months) from the start of induction therapy; however, fatal treatment-related toxicities also occurred in 4 patients (20%). Three patients died as a result of a progressive encephalopathy which, in 2 instances, was accompanied by a wasting syndrome; 1 patient died as a consequence of an intracerebral (intratumoral) hemorrhage. Fatal toxicities occurred in patients with pretreatment Karnofsky scores of 60 or 70. High-dose thiotepa to consolidate response was a disappointing treatment strategy for patients with recurrent aggressive oligodendroglial neoplasms, although several patients had durable responses. Moreover, as prescribed, high-dose thiotepa had significant toxic effects in previously irradiated patients, especially those with poorer performance status.